Riemann-Liouville and Higher Dimensional Hardy Operators for NonNegative Decreasing Function in Lp(·) Spaces. (26th August 2014) - Sarwar, Muhammad; Murtaza, Ghulam; Ahmed, Irshaad
Abstract : One-weight inequalities with general weights for Riemann-Liouville transform and n -dimensional fractional integral operator in variable exponent Lebesgue spaces defined on R n are investigated. In particular, we derive necessary and sufficient conditions governing one-weight inequalities for these operators on the cone of nonnegative decreasing functions in L p ( x ) spaces.